Intraday Price Formation in U.S. Equity Index Markets - Hasbrouck, Joel (Journal of Finance, 2003)
Abstract The market for U.S. equity indexes presently comprises floor‐traded index futures contracts, exchange‐traded funds (ETFs), electronically traded, small‐denomination futures contracts (E‐minis), and sector ETFs that decompose the S&P 500 index into component industry portfolios. This paper empirically investigates price discovery in this environment. For the S&P 500 and Nasdaq‐100 indexes, most of the price discovery occurs in the E‐mini market. For the S&P 400 MidCap index, price discovery is shared between the regular futures contract and the ETF. The S&P 500 ETF contributes markedly to price discovery in the sector ETFs, but there are only minor effects in the reverse direction.